2006
DOI: 10.1007/s10327-005-0255-7
|View full text |Cite
|
Sign up to set email alerts
|

Race distribution of Phytophthora sojae on soybean in Hyogo, Japan

Abstract: Since 1987, Phytophthora root and stem rot of soybean [Glycine max (L.) Merr. cv. Tanbakuro], caused by Phytophthora sojae Kaufman and Gerdemann, has been increasing in the Sasayama, Nishiwaki, and Kasai regions in Hyogo, the most famous soybean (cv. Tanbakuro)-producing areas in Japan. In 2002 to 2004, 51 isolates (one from each field) of P. sojae were recovered from 51 fields in Hyogo. These isolates were tested for virulence on six Japanese differential soybean cultivars used for race determination in Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 14 publications
1
51
0
Order By: Relevance
“…Isolates PJ-H65, PJ-H30, PJ-H5M, PJ-H42, and PJ-H67 were selected for disease experiments because Sugimoto et al (2006) had previously found these four isolates to be highly virulent on Tanbakuro (95-100%), and to induce different reactions on six Japanese differential cultivars ('Isuzu','Kitamusume','Toyosuzu',and 'Ohhojyu'). Seven additional isolates also were added for the virulence examinations: T-4 was obtained from Dr. H. Mukobata of the Toyama Prefectural Agricultural, Forestry and Fisheries Research Center; Shonai-3 was obtained from Dr. S. Koizumi of the National Agricultural Research Center for the Tohoku Region; and five isolates representing races 1 (R1), 4 (R4), 7 (R7), 17 (R17), 25 (R25) were obtained from Dr. A. Dorrance of the Department of Plant Pathology at The Ohio State University, USA.…”
Section: Pathogens Used In This Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Isolates PJ-H65, PJ-H30, PJ-H5M, PJ-H42, and PJ-H67 were selected for disease experiments because Sugimoto et al (2006) had previously found these four isolates to be highly virulent on Tanbakuro (95-100%), and to induce different reactions on six Japanese differential cultivars ('Isuzu','Kitamusume','Toyosuzu',and 'Ohhojyu'). Seven additional isolates also were added for the virulence examinations: T-4 was obtained from Dr. H. Mukobata of the Toyama Prefectural Agricultural, Forestry and Fisheries Research Center; Shonai-3 was obtained from Dr. S. Koizumi of the National Agricultural Research Center for the Tohoku Region; and five isolates representing races 1 (R1), 4 (R4), 7 (R7), 17 (R17), 25 (R25) were obtained from Dr. A. Dorrance of the Department of Plant Pathology at The Ohio State University, USA.…”
Section: Pathogens Used In This Studymentioning
confidence: 99%
“…A total of 77 isolates of P. sojae were identified from 77 infected soybean plants collected from several soybean-producing fields in Hyogo between 2002 and 2006 using the method described by Sugimoto et al (2006), and these isolates were tested for virulence towards Tanbakuro using the agar medium inoculation method described in that paper. Isolates PJ-H65, PJ-H30, PJ-H5M, PJ-H42, and PJ-H67 were selected for disease experiments because Sugimoto et al (2006) had previously found these four isolates to be highly virulent on Tanbakuro (95-100%), and to induce different reactions on six Japanese differential cultivars ('Isuzu','Kitamusume','Toyosuzu',and 'Ohhojyu').…”
Section: Pathogens Used In This Studymentioning
confidence: 99%
See 3 more Smart Citations